Pengaruh Diferensiasi Produk, Brand Equity, Dan Brand Positioning Terhadap Keputusan Pembelian Skincare MS Glow Man Di Madiun - Yudhistira, Ivanda Danar; Farida, Eka; Athia, Ita (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to determine whether product differentiation, brand equity and brand positioning have a simultaneous effect on consumer purchasing decisions for MS Glow Man skincare in Madiun. The type of research used in this study is explanatory research with a quantitative approach method. The population of this study is consumers of MS Glow Man skincare users in Madiun City whose number is unknown. Determination of the number of samples used in this study will use the Malhotra formula, because it can be considered appropriate. The number of samples taken can be determined by multiplying the number of variables/indicators 18 by 5, so the minimum sample is 18 x 5, which is 90 respondents. The results of the study showed that product differentiation, brand equity, and brand positioning simultaneously and partially had a significant effect on purchasing decisions. Keywords: Product Differentiation, Brand Equity, Brand Positioning, And Purchasing Decisions